2015
DOI: 10.3390/nano5020656
|View full text |Cite
|
Sign up to set email alerts
|

Structural Ceramic Nanocomposites: A Review of Properties and Powders’ Synthesis Methods

Abstract: Ceramic nanocomposites are attracting growing interest, thanks to new processing methods enabling these materials to go from the research laboratory scale to the commercial level. Today, many different types of nanocomposite structures are proposed in the literature; however, to fully exploit their exceptional properties, a deep understanding of the materials’ behavior across length scales is necessary. In fact, knowing how the nanoscale structure influences the bulk properties enables the design of increasing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
90
0
13

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(106 citation statements)
references
References 159 publications
3
90
0
13
Order By: Relevance
“…Smaller grains can limit the size of the dislocations on the crystal grain boundaries, thus increasing mechanical properties. 16,21,22 Based on the FS values, ISO standard 6872-2015 would grade the 5Y-PSZ groups as class 4 materials to be utilized as single-unit anterior or posterior prostheses or as a 3-unit anterior prosthesis. 23 After fatigue testing, Katana UTML, would be re-classified as a class 2 ceramic, with recommendation to be utilized as an adhesively cemented anterior or posterior single-unit crown owing to its significant decrease in strength.…”
Section: Discussionmentioning
confidence: 99%
“…Smaller grains can limit the size of the dislocations on the crystal grain boundaries, thus increasing mechanical properties. 16,21,22 Based on the FS values, ISO standard 6872-2015 would grade the 5Y-PSZ groups as class 4 materials to be utilized as single-unit anterior or posterior prostheses or as a 3-unit anterior prosthesis. 23 After fatigue testing, Katana UTML, would be re-classified as a class 2 ceramic, with recommendation to be utilized as an adhesively cemented anterior or posterior single-unit crown owing to its significant decrease in strength.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the authors also has been reported that the SiC-ZrO 2 microstructure refinement with harmonic grain dispersion indicate superior mechanical properties [7,8]. Thus, if the composite can be made into a nano/nano or a nano/micro type, additional improvement in toughness and strength can be expected because of the change of fracture mode of the composite which act to deflect or stop the crack propagation [9], as shown in Fig. 2.…”
Section: Introductionmentioning
confidence: 94%
“…Much effort has been paid to improve fracture toughness of ceramics using micro‐ and nanostructures as reinforcements. These methods have the similar aim of providing additional intrinsic grain boundaries or extrinsic interfaces that prohibit dislocation movement and long paths of crack propagation . Conventionally, one‐dimensional materials, including carbon fibers, carbon nanotubes, and silicon carbide whiskers, are used as the reinforcements in the ceramic matrix composites, in which fiber pullout, fiber bridging, and crack deflection are considered as the main toughening mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…These methods have the similar aim of providing additional intrinsic grain boundaries or extrinsic interfaces that prohibit dislocation movement and long paths of crack propagation. 1,2 Conventionally, one-dimensional materials, including carbon fibers, carbon nanotubes, and silicon carbide whiskers, are used as the reinforcements in the ceramic matrix composites, in which fiber pullout, fiber bridging, and crack deflection are considered as the main toughening mechanisms. Although the above toughening mechanisms have changed crack paths and thus enhanced fracture toughness of ceramics, they can come into play in only one-dimensional direction.…”
Section: Introductionmentioning
confidence: 99%